The Influence of Imagery Training Methods on Pointing Accuracy Results in Petanque Athletes - Abdullah, Abdullah; Samsudin, Samsudin; Nasrullah, Nasrullah; Mulyadi, Mulyadi; Irawan, Ewan (Champions: Education Journal of Sport, Health, and Recreation, 2024)
The aim of this study is to know the influence of imagery training methods on the accuracy pointing results on petanque athletes STKIP Taman Siswa Bima. This study is an experimental study with the design of the research is "The One Group Pretest-Posttest Design". The population in this study are petanques athlete STKIP Taman Siswa Bima which amounts to 10 athlets. The sample was taken using a non-probability technique, a saturated sampling of 10 athletes. Data analysis using descriptive statistics, pre-conditional tests, and test-t. The results of analysis showed that there was a significant influence of the results of the imagery training method on the pointing accuracy result, with t count=6,504 > t table = 1,859 and the significance value of 0,000 < 0,05. It was concluded that the imagers training method had a significant impact on the pointsing accurate result in petanque athletes STKIP Taman Siswa Bima.